Professional issues in information technology - Bott, Frank (British Computer Society, 2014)
This book addresses the social, legal, financial, organisational and ethical issues relevant to IT professionals. It is designed to accompany the BCS HEQ 'Diploma in IT' core module: Professional Issues in Information Systems Practice. This new edition covers the social and legal implications of recent changes to legislation and technology.
Includes bibliographical references and index
Keywords: Information technology; Information technology -- Vocational guidance; Management; Technologie de l'information; Technologie de l'information; Orientation professionnelle; Gestion; information technology; management; Information technology; Vocational guidance